2003
DOI: 10.2308/iace.2003.18.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Dickinson Technologies, Inc.: Assessing Control Environment and Fraud Risk

Abstract: This instructional case provides you an opportunity to perform realistic audit tasks using evidence obtained from an actual company. Through the use of engaging materials, the case helps you to develop an understanding of the control environment concepts presented in SAS No. 78 (AICPA 1995), Consideration of Internal Control in a Financial Statement Audit, and fraud risk assessment presented in SAS No. 99 (AICPA 2002), Consideration of Fraud in a Financial Statement Audit. This case involves making a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…1). First, both groups of students were given a traditional lecture 7 The case we used was Dickinson Technologies (Agoglia, Brown, & Hanno, 2003). We chose this case because the answers were not ''black and white,'' and the students have to carefully scrutinize the materials before making a risk assessment based on professional judgment.…”
Section: Between-subjects Assessmentmentioning
confidence: 99%
“…1). First, both groups of students were given a traditional lecture 7 The case we used was Dickinson Technologies (Agoglia, Brown, & Hanno, 2003). We chose this case because the answers were not ''black and white,'' and the students have to carefully scrutinize the materials before making a risk assessment based on professional judgment.…”
Section: Between-subjects Assessmentmentioning
confidence: 99%
“…Some studies have examined how audit evidence of the control environment impacts audit judgements (e.g., Agoglia et al 2003;Bernardi 1994;Cohen and Hanno;Schmidt 2014). For example, some studies (Cohen and Hanno, 2000) have shown that two important elements of the control environment (management control philosophy and governance structure) impact pre-planning and planning judgements and can prove useful in developing work papers and risk assessment models.…”
Section: Introductionmentioning
confidence: 99%
“…experiment began with brief instructions asking participants to assume the role of the auditor involved in the preplanning stage of an integrated audit of a hypothetical client. They then read Part A of the experimental materials that contained a common set of background information adapted from prior research to reflect the current economic environment (with permissions fromAgoglia, Brown, & Hanno, 2003;McCracken et al, 2011). The background information included a brief introduction of the client management team, board of directors and audit committee.…”
mentioning
confidence: 99%